A new device for assessment and training the human balance and coordination: Marmara Balance and Education System (MarBES) - KURU ÇOLAK, TUĞBA; ÖZEN BERKOL, TUĞÇE; GÜNAY YAZICI, CANAN; SARI, ZÜBEYİR; POLAT, MİNE GÜLDEN; DOĞAN, BARIŞ; TARIM, MEHVEŞ (My University, 2023)
© 2023, The Author(s), under exclusive licence to Royal Academy of Medicine in Ireland.Background: Balance and coordination are important for performing activities of daily living. Balance and coordination assessment and training are used by physiotherapists in many different rehabilitation areas. Marmara Balance and Education System (MarBES) is a device developed to evaluate and improve balance and coordination. Aims: To examine the test–retest reliability of the MarBES device. Methods: Double-leg and single-leg (eyes open-closed) tests were applied to healthy young adult participants for balance testing on the MarBES device. Weight data is estimated from pressure sensors located in 4 different corners and a score is calculated with computer software for the individual’s center of gravity (center of pressure X, Y) and the amount of deviation from the center for each axis. Weight transfer to the target surface was measured for assessment of the participants’ coordination performance. Participants rested for 10 min and all measurements were repeated by the same evaluator. The obtained data were recorded and the reliability of the measurements was evaluated with Spearman’s rho correlation analysis. Results: A total of 40 healthy young individuals (28 female) with a mean age of 21 years were included. The balance assessments with MarBES showed moderate to good reliability (ICC: 0.535–0.903). The coordination assessment results showed moderate to good reliability (ICC: 0.575–0.712). Conclusions: Objective evaluation of balance and coordination parameters is very important in rehabilitation. Results of the study showed that the MarBES device developed by the researchers is a reliable method for the evaluation of balance and coordination in healthy young individuals.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Balance; Coordination; Rehabilitation; Reliability